PENGARUH PEMBIAYAAN BAGI HASIL TERHADAP KINERJA BANK SYARIAH - Roby Prabowo (2017)
This study was conducted to examine the effect of mudharabah and musyarakah on Islamic bank performance. This study uses the Islamic banks listed in Indonesian bank as a sample. Sampling technique using purposive sampling (purposive sampling method). Selection of a sample of 11 islamic banks listed in Indonesian Bank resulted in 10 banks that are acceptable. Testing the hypothesis in this study using Multiple Linear Regression Analysis with SPSS 21 and a significance level of 5 %. The results of the testing showed that: (1) mudharabah has a significant influence on the Islamic bank performance with a significance level of 0.001 is smaller than the specified level α = 0.05. (2) musyarakah has significant effect on the Islamic bank performance because it has a significance level of 0.006 is smaller than the specified level α = 0.05.